Cikakembang River Restoration from the Perspective of Numerical Modelling - Kent, Steven; Yudianto, Doddi; Gao, Cheng; Fitriana, Finna; Wang, Qian (Universitas Mercu Buana, 2025)
The poor condition of the Citarum River demands more significant pollution control. One alternative for controlling pollution can be limiting the amount of wastewater entering one of the tributaries of the Citarum River, namely the Cikakembang River. This study is a follow-up study that will model heavy metal parameters in the Cikakembang River. Data collection was carried out six times, where the heavy metal parameter detected was copper. Numerical modelling for copper parameters was carried out using MATLAB software with the Runge Kutte-4 discretisation scheme. The study location covers 2.36 km upstream of the Cikakembang River, with 12 textile industry wastewater disposal points. Numerical modelling results for copper parameters show a settling rate of heavy metal particles of 40 day-1, with a maximum RRMSE value of 9.97%. Combining the water quality models for organic and heavy metal parameters created, pollution control simulations can be run in both seasons. The pollution control scenario aims to find the maximum amount that enters the Cikakembang River without passing the class four river water quality standards. The selection of the standard is based on the use of Cikakembang River water, namely for irrigation purposes. Based on the results of pollution control simulations, the pollutant carrying capacity for BOD, COD and copper parameters in the Cikakembang River is 199.43 kg/day, 1103.80 kg/day and 4.06 kg/day, respectively.